Fresh-frozen allogeneic bone blocks grafts for alveolar ridge augmentation: Biological and clinical aspects - Stavropoulos, Andreas; Marcantonio, Camila Chierici [UNESP]; de Oliveira, Vithor Xavier Resende; Marcantonio, Élcio [UNESP]; de Oliveira, Guilherme José Pimentel Lopes (Wiley, 2023)
The possibilities for oral bone regeneration procedures vary depending on the type of bone defect to be treated, which in turn dictate the type of graft to be used. Atrophic alveolar ridges are non-contained defects and pose a challenging defect morphology for bone regeneration/augmentation. Successful results are regularly obtained with the use of particulate grafts in combination with barrier membranes. In cases of very narrow ridges with need of larger amount of bone augmentation, block grafts are often used. Fresh-frozen allogeneic bone block grafts have been proposed as an alternative to autogenous (AT) bone blocks. Based on a systematic appraisal of pre-clinical in vivo studies and clinical trials including a direct comparison of fresh-frozen bone (FFB) blocks versus AT bone blocks it can be concluded that a FFB block graft: (a) cannot be considered as a reliable replacement of a AT bone block, and (b) should only be considered in cases where the amount of necessary augmentation—in a lateral direction—is relatively limited, so that the main portion of the body of the implant lies within the inner (i.e., the vital) aspect of the block.
Keywords: autogenous bone; block bone graft; fresh-frozen bone allograft